2009
DOI: 10.2337/dc08-1980
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Duration, Lifestyle Intervention, and Incidence of Type 2 Diabetes in Impaired Glucose Tolerance

Abstract: OBJECTIVEBoth short and long sleep duration have frequently been found to be associated with an increased risk for diabetes. The aim of the present exploratory analysis was to examine the association between sleep duration and type 2 diabetes after lifestyle intervention in overweight individuals with impaired glucose tolerance in a 7-year prospective follow-up.RESEARCH DESIGN AND METHODSA total of 522 individuals (aged 40–64 years) were randomly allocated either to an intensive diet-exercise counseling group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
56
4
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(64 citation statements)
references
References 25 publications
3
56
4
1
Order By: Relevance
“…After evaluating the full texts of these 14 publications, we further excluded 4 articles (10,11,28,29) due to a lack of sufficient data for estimation of dose-response analysis. In addition, we included the report of the control group, and not the intervention group, in the study by Tuomilehto et al (18). In the study by Kita et al (16), the results were separated according to the presence or absence of a family history of diabetes (FHD), so we treated it as two separate reports.…”
Section: Data Synthesis and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…After evaluating the full texts of these 14 publications, we further excluded 4 articles (10,11,28,29) due to a lack of sufficient data for estimation of dose-response analysis. In addition, we included the report of the control group, and not the intervention group, in the study by Tuomilehto et al (18). In the study by Kita et al (16), the results were separated according to the presence or absence of a family history of diabetes (FHD), so we treated it as two separate reports.…”
Section: Data Synthesis and Analysismentioning
confidence: 99%
“…In addition, without a dose-response analysis, it remains unknown how many hours of habitual sleep are associated with the lowest risk of type 2 diabetes. In the past several years, the number of prospective studies with enough quantitative categories has nearly doubled (13)(14)(15)(16)(17)(18)(19)(20)(21)(22). Therefore, we conducted a meta-analysis of prospective studies to determine the overall shape of the relationship between sleep duration and risk of type 2 diabetes.…”
mentioning
confidence: 99%
“…There is a complicated relationship between obesity, diabetes, depression, and obstructive sleep apnoea. 18,19 Sleep disturbances in diabetes are frequently due to nocturia, neurogenic pain, and other causes. 20,21 The PHQ-9 questions about over eating or under eating, and the somatic symptom of tiredness may be accounted for by diabetes itself, or by sleep disturbances including obstructive sleep apnoea, and could account for the high classification rate for moderate to severe depression.…”
Section: Implications For Clinical Practice and Future Researchmentioning
confidence: 99%
“…Proceedings of the Nutrition Society developing T2DM, studied over varying lengths of followup (7)(8)(9)(10)(11)(12)(13)(14)(15)(16) . Details of their study design and outcomes are shown in Table 1.…”
Section: Association Between Sleep Duration and The Risk Of Type 2 DImentioning
confidence: 99%
“…Another prospective study examined the association of sleep duration with development of impaired fasting glucose over 6 years follow-up (11) , with 6-8 h sleep duration as a reference category, short (but not long) sleepers had higher odds of developing impaired fasting glucose (OR 3·0, 95 % CI 1·05, 8·59; OR 1·6, 95 % CI 0·45, 5·42 for short and long sleep durations, respectively). A Finnish study in overweight individuals with impaired glucose tolerance found an increased risk of T2DM only in participants with long sleep duration ⩾9 h (hazard ratio (HR) 2·29, 95 % CI 1·38, 3·80) (14) . Finally, two recent meta-analyses of nine (17) and fourteen (18) prospective cohort studies have also confirmed the U-shaped relationship (Fig.…”
Section: Association Between Sleep Duration and The Risk Of Type 2 DImentioning
confidence: 99%